Investigating The Use Of Whatsapp To Improve The Writing Skills Of Students At King Abdul Aziz University - Alouch, Malek (2020)
The use of the WhatsApp application has become increasingly crucial in education. It has enabled administrators and instructors to contact students for administrative and educational reasons and purposes. The purpose of this study is to investigate to what extent the use of WhatsApp improves students’ writing skills and to identify students’ perceptions regarding the use of WhatsApp to learn and practice writing skills inside the classroom. The intervention was done is a class of level 104 students at the English Language Institute, King Abdul Aziz University.